Globalisation, E-learning and the Monetary Pressure on the Educational Field - Salvatore Pasquale Angilletta (Social Work & Society, 2005)
Globalisation, this is my thesis, change first the trade of goods and services, produce a mercantilist pressure on different political fields and affect finally as a consequence effectively our normative comprehension of education. As states will be more and more under pressure to compete on an economic basis against each other they will rank decisions which generate jobs higher than any thing else. Also Education policy is changing its focus. E-learning is a driving force to bring together education, trade of ICT equipment, trade of educational used content and trade of study degrees and to merge the different objectives into effective distribution of knowledge and maximising profits.